Spectral induced polarization of corrosion of sulfur modified Iron in sediments - Hilary P. Emerson; James E. Szecsody; Christopher Halter; Judy L. Robinson; Jonathan N. Thomle; Mark E. Bowden; Odeta Qafoku; C. Tom Resch; Lee D. Slater; Vicky L. Freedman (Journal of Contaminant Hydrology, 2024)

OS01-12 A computational toolbox supporting the development of Safe and Sustainable by Design chemicals and materials - D. Sarigiannis; F. Nikiforou; A. Karakoltzidis; A. Agalliadou; T. Rydberg; M. Halling; C.L. Battistelli; E. Benfenati; C. Bossa; E. Bouman; É. Bourgé; M. Brouwer-Milovanovic; et al. (Toxicology Letters, 2024)

Safety-by-design and engineered nanomaterials: the need to move from theory to practice - Benjamin D. Trump; Dalila Antunes; José Palma-Oliveira; Andrew Nelson; Alexandra Misci Hudecova; Elise Rundén-Pran; Maria Dusinska; Ignasi Gispert; Susanne Resch; Beatriz Alfaro-Serrano; Antreas Afantitis; Georgia Melagraki; et al. (Environment Systems and Decisions, 2024)
As the governance of engineered nanomaterials (ENMs) evolves, innovations in the prevention, mitigation, management, and transfer of risk shape discussion of how nanotechnology may mature and reach various marketplaces. Safety-by-Design (SbD) is one leading concept that, while equally philosophy as well as risk-based practice, can uniquely help address lingering uncertainties and concerns stemming from regulatory evaluation of ENM risk across worker, consumer, and environmental safety. This paper provides a discussion on the SbD concept across different disciplines aiming to identify different approaches and needs to meet regulatory requirements—ultimately, we argue that SbD is evolving both to meet the needs and discourse of various disciplines, and to apply within differing marketplaces and national regulatory structures. Understanding how SbD has evolved within ENM can yield a more practical application and development of SbD, and help guide or unify national and international ENM governance around a core set of safety-driven principles.

Psychometric Properties of Computerized Cognitive Tools and Standard Neuropsychological Tests Used to Assess Sport Concussion: A Systematic Review - Kristin Wilmoth; Benjamin L. Brett; Natalie A. Emmert; Carolyn M. Cook; Jeffrey Schaffert; Todd Caze; Thomas Kotsonis; Margaret Cusick; Gary Solomon; Jacob E. Resch; C. Munro Cullum; Lindsay D. Nelson; et al. (Neuropsychology Review, 2023)

Correction to: Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)

Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)
Climate change scenarios predict more frequent and intense drought periods for 2071 to 2100 for many regions of the world including Austria. Current and predicted lower precipitation scenarios were simulated at a lysimeter station containing a fertile and less fertile agricultural soil for 9 years. 13 C and 15 N-labeled green manure was added in year 8 with the aim to analyze how the predicted precipitation regime affects soil fauna and microbial groups and consequently nitrogen (N) and carbon (C) cycling. Among the investigated mesofauna (collembola and oribatida), the abundance and biodiversity of oribatida was significantly reduced by drought, possibly because they mainly represent K-strategist species with low mobility and consequently the need to adapt to long-term adverse environmental conditions. Microbial community composition and microbial biomass, investigated by phospholipid fatty acid (PLFA) analysis, was indistinguishable between the current and the predicted precipitation scenarios. Nonetheless, soil 13 C-CO 2 emissions and soil water 15 N-NO 3 data revealed decelerated mineralization of green manure under reduced precipitation in the first 2 weeks, but no effects were observed on soil C sequestration or on 13 C incorporation into microbial PLFAs in the following 1.2 years. We found that over a 1-year time period, decomposition was rather driven by plant residue availability than water limitation of microorganisms in the investigated agroecosystem. In contrast, N 2 O emissions were significantly reduced under drought, and green manure derived 15 N accumulated in the soil under drought, which might necessitate the adjustment of future fertilization regimes. The impacts of reduced precipitation and drought were less pronounced in the more fertile agricultural soil, due to its greater buffering capacity in terms of water storage and organic matter and nutrient availability.

Functional Zoning by Site Index to Balance Multiple Objectives for Pine in Southern US Family Forests - Bradley S Resch; Austin Himes; Stephen C Grado; Robert K Grala; Bruno Kanieski da Silva (Journal of Forestry, 2023)
Family forests comprise a significant portion of total forest land area in the southern United States and their owners frequently have multiple, competing objectives. This research evaluated the effectiveness of functional zoning based on site index on forest sizes relevant to family forest owners. A total of fifty family forests were randomly selected from twenty-five counties in the East Texas Pineywoods region. Timber production and northern bobwhite habitat (Colinus virginianus) habitat were used as proxies for competing objectives. It was found that 80% of family forest parcels had sufficient site index heterogeneity to benefit from functional zoning. For forest parcels that could benefit from functional zoning, the benefit in terms of increased land expectation value (LEV) was not found to be dependent on parcel size. On average, this approach increased the LEV $32/ac at a 3% discount rate, $16/ac at 5%, and $9/ac at 7%. This zoning approach supports multiple objectives while minimizing the economic impact of the nonrevenue objectives.

To Waste or Not to Waste: Questioning Potential Health Risks of Micro- and Nanoplastics with a Focus on Their Ingestion and Potential Carcinogenicity - Elisabeth S. Gruber; Vanessa Stadlbauer; Verena Pichler; Katharina Resch-Fauster; Andrea Todorovic; Thomas C. Meisel; Sibylle Trawoeger; Oldamur Hollóczki; Suzanne D. Turner; Wolfgang Wadsak; A. Dick Vethaak; Lukas Kenner (Exposure and Health, 2023)
Micro- and nanoplastics (MNPs) are recognized as emerging contaminants, especially in food, with unknown health significance. MNPs passing through the gastrointestinal tract have been brought in context with disruption of the gut microbiome. Several molecular mechanisms have been described to facilitate tissue uptake of MNPs, which then are involved in local inflammatory and immune responses. Furthermore, MNPs can act as potential transporters (“vectors”) of contaminants and as chemosensitizers for toxic substances (“Trojan Horse effect”). In this review, we summarize current multidisciplinary knowledge of ingested MNPs and their potential adverse health effects. We discuss new insights into analytical and molecular modeling tools to help us better understand the local deposition and uptake of MNPs that might drive carcinogenic signaling. We present bioethical insights to basically re-consider the “culture of consumerism.” Finally, we map out prominent research questions in accordance with the Sustainable Development Goals of the United Nations.

Aldosterone-sensitive HSD2 neurons in mice - Silvia Gasparini; Jon M. Resch; Sowmya V. Narayan; Lila Peltekian; Gabrielle N. Iverson; Samyukta Karthik; Joel C. Geerling (Brain Structure and Function, 2019)

Respiratory syncytial virus-associated hospitalization rates in high-risk populations: an observational comparative cohort analysis - B. Resch; C. Puchas; B. Urlesberger (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Physiology of the Vc-NhaP paralogous group of cation–proton antiporters in Vibrio cholerae - Muntahi Mourin; Carla B. Schubiger; Craig T. Resch; Claudia C. Häse; Pavel Dibrov (Molecular and Cellular Biochemistry, 2017)

Deterministic influences exceed dispersal effects on hydrologically‐connected microbiomes - Emily B. Graham; Alex R. Crump; Charles T. Resch; Sarah Fansler; Evan Arntzen; David W. Kennedy; Jim K. Fredrickson; James C. Stegen (Environmental Microbiology, 2017)
Summary Subsurface groundwater‐surface water mixing zones (hyporheic zones) have enhanced biogeochemical activity, but assembly processes governing subsurface microbiomes remain a critical uncertainty in understanding hyporheic biogeochemistry. To address this obstacle, we investigated (a) biogeographical patterns in attached and waterborne microbiomes across three hydrologically‐connected, physicochemically‐distinct zones (inland hyporheic, nearshore hyporheic and river); (b) assembly processes that generated these patterns; (c) groups of organisms that corresponded to deterministic changes in the environment; and (d) correlations between these groups and hyporheic metabolism. All microbiomes remained dissimilar through time, but consistent presence of similar taxa suggested dispersal and/or common selective pressures among zones. Further, we demonstrated a pronounced impact of deterministic assembly in all microbiomes as well as seasonal shifts from heterotrophic to autotrophic microorganisms associated with increases in groundwater discharge. The abundance of one statistical cluster of organisms increased with active biomass and respiration, revealing organisms that may strongly influence hyporheic biogeochemistry. Based on our results, we propose a conceptualization of hyporheic zone metabolism in which increased organic carbon concentrations during surface water intrusion support heterotrophy, which succumbs to autotrophy under groundwater discharge. These results provide new opportunities to enhance microbially‐explicit ecosystem models describing hyporheic zone biogeochemistry and its influence over riverine ecosystem function.

Computerized Neurocognitive Testing in the Management of Sport-Related Concussion: An Update - Jacob E. Resch; Michael A. McCrea; C. Munro Cullum (Neuropsychology Review, 2013)

Two nosocomial norovirus outbreaks in the neonatal intensive and intermediate care unit - C. Sommer; W. Mueller; B. Resch (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Perivascular cells of the supraspinatus tendon express both tendon- and stem cell-related markers - Herbert Tempfer; A. Wagner; R. Gehwolf; C. Lehner; M. Tauber; H. Resch; H. C Bauer (Histochemistry and Cell Biology, 2009)

The Calibration Kit Spectral Fluorescence Standards—A Simple and Certified Tool for the Standardization of the Spectral Characteristics of Fluorescence Instruments - D. Pfeifer; K. Hoffmann; A. Hoffmann; C. Monte; U. Resch-Genger (Journal of Fluorescence, 2006)

Traceability in Fluorometry: Part II. Spectral Fluorescence Standards - U. Resch-Genger; D. Pfeifer; C. Monte; W. Pilz; A. Hoffmann; M. Spieles; K. Rurack; J. Hollandt; D. Taubert; B. Schönenberger; P. Nording (Journal of Fluorescence, 2005)

Traceability in Fluorometry—Part I: Physical Standards - J. Hollandt; R. D. Taubert; J. Seidel; U. Resch-Genger; A. Gugg-Helminger; D. Pfeifer; C. Monte; W. Pilz (Journal of Fluorescence, 2005)

Comparative analysis of satellite cell properties in heavy- and lightweight strains of turkey - F. Merly; C. Magras-Resch; T. Rouaud; J. Fontaine-Perus; M. F. Gardahaut (Journal of Muscle Research and Cell Motility, 1998)

Typical Frankia infect actinorhizal plants exotic to New Zealand - Michael L. Clawson; David R. Benson; Steven C. Resch; David W. Stephens; Warwick B. Silvester (New Zealand Journal of Botany, 1997)
Frankia strains are actinomycetes that fix N 2 in root nodules of plants classified in eight families of the Angiospermae. The wide variety of plants infected has raised questions about the ecology and diversity of Frankia symbionts, and their co‐evolution with actinorhizal plants. Partial sequencing was done of the small subunit (16S) rRNA gene from Frankia endophytes present in the root nodules of Alnus cordata , A. glutinosa , A. viridis , Casuarina equisetifolia, Coriaria arborea, C. plumosa , and Elaeagnus pungens growing in New Zealand. With the exceptions of the Coriaria spp., all of the plants are exotic to New Zealand. Analysis of the 16S rRNA gene indicates that the exotic species were nodulated by Frankia strains that cluster with strain groups previously shown to be typical for each actinorhizal host. Frankia in 12 native Coriaria spp. nodules yielded two sequences differing in only one position, suggesting a relatively low diversity compared with the exotic species.

Ammonia uptake and retention in some cyanobacteria - S. Boussiba; C. M. Resch; J. Gibson (Archives of Microbiology, 1984)